Abundant Allelochemicals and the Inhibitory Mechanism of the Phenolic Acids in Water Dropwort for the Control of Microcystis aeruginosa Blooms - Jixiang Liu; Yajun Chang; Linhe Sun; Fengfeng Du; Jian Cui; Xiaojing Liu; Naiwei Li; Wei Wang; Jinfeng Li; Dongrui Yao (Plants, 2021)
In recent years, with the frequent global occurrence of harmful algal blooms, the use of plant allelopathy to control algal blooms has attracted special and wide attention. This study validates the possibility of turning water dropwort into a biological resource to inhibit the growth of harmful Microcystis aeruginosa blooms via allelopathy. The results revealed that there were 33 types of allelopathic compounds in the water dropwort culture water, of which 15 were phenolic acids. Regarding water dropwort itself, 18 phenolic acids were discovered in all the organs of water dropwort via a targeted metabolomics analysis; they were found to be mainly synthesized in the leaves and then transported to the roots and then ultimately released into culture water where they inhibited M. aeruginosa growth. Next, three types of phenolic acids synthesized in water dropwort, i.e., benzoic, salicylic, and ferulic acids, were selected to clarify their inhibitory effects on the growth of M. aeruginosa and their mechanism(s) of action. It was found that the inhibitory effect of phenolic acids on the growth of M. aeruginosa increased with the increase of the exposure concentration, although the algae cells were more sensitive to benzoic acid than to salicylic and ferulic acids. Further study indicated that the inhibitory effects of the three phenolic acids on the growth of M. aeruginosa were largely due to the simultaneous action of reducing the number of cells, damaging the integrity of the cell membrane, inhibiting chlorophyll a (Chl-a) synthesis, decreasing the values of F0 and Fv/Fm, and increasing the activity of the antioxidant enzymes (SOD, POD, and CAT) of M. aeruginosa. Thus, the results of this study indicate that both culture water including the rich allelochemicals in water dropwort and biological algae inhibitors made from water dropwort could be used to control the growth of noxious algae in the future.